Ergonomics hazard analysis techniques- A technical review. (2021) - Ramaganesh, M.; Jayasuriyan, R.; Rajpradeesh, T.; Bathrinath, S.; Manikandan, R.
Abstract: The article aims to review the various Ergonomics studies carried out in various domains mainly focusing on preventing the incidents and accidents that will lead to the human factors and ergonomics problems faced by the industrial workers. The various researchers have identified various tools to improve the ergonomic interventions methods to overcome and decrease the incident frequency. Although safety is a very relevant contribution to their ergonomics and human parts, this article is discussed based on the various industrial zones. After that, a clear way of mitigation and prevention methods can be implemented in the workplace. A workplace that deals with the machinery part interacts with the environment with the comfort level zones. Especially in the manufacturing industry, ergonomics is prominent human factors. This article reviewed various methodology proposed in various industries based on the postures and awkward frequencies of each work activity. Each research tool defines different comfort level zones that interact with the workers. Based on that, only future work carried out, and problems were extensively identified by the previous literature.